Modelling and Control of Discrete Event Dynamic Systems - Capkovic, Frantisek (BRICS Report Series, 2000)
Discrete event dynamic systems (DEDS) in general are investigated as to their analytical models most suitable for control purposes and as to the analytical methods of the control synthesis. The possibility of utilising both the selected kind of Petri nets and the oriented graphs on this way is pointed out. Because many times the control task specifications (like criteria, constraints, special demands, etc.) are given only verbally or in another form of non analytical terms, a suitable knowledge representation about the specifications is needed. Special kinds of Petri nets (logical, fuzzy) are suitable on this way too. Hence, the knowledge-based control synthesis of DEDS can also be examined. The developed graphical tools for model drawing and testing as well as for the automated knowledge-based control synthesis are described and illustratively presented. Two approaches to modelling and control synthesis based on oriented graphs are developed. They are suitable when the system model is described by the special kind of Petri nets - state machines. At the control synthesis the first of them is straightforward while the second one combines both the straight-lined model dynamics development (starting from the given initial state towards the prescribed terminal one) and the backtracking model dynamics development.